Perinatal inflammation and lung injury - Viscardi, Rose Marie (2011)
Bronchopulmonary dysplasia (BPD) remains the major morbidity of extreme preterm birth. The incidence of BPD has remained stable despite recent efforts to reduce postnatal exposures to volutrauma and hyperoxia. This review will focus on recent clinical and experimental insights that provide support for the concept that the ‘new BPD’ is the result of inflammation-mediated injury and altered lung development during a window of vulnerability in genetically susceptible infants that is modified by maternal and postnatal exposures.